MEASURING ACCURACY AND COMPLEXITY OF AN L2 LEARNER’S ORAL PRODUCTION - Teguh Khaerudin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
This paper aims at examining the influence of different tasks on the degree of task performance in a second language learner’s oral production. The underlying assumption is that among the three aspects of language performance in L2, i.e. fluency, accuracy, and complexity, learners may prioritize only one of them (Ellis & Barkhuizen, 2005, p. 150) and that their decision to prioritize one particular area of language performance may be determined by the characteristics of the task given to the learners (Skehan & Foster, 1997). Having a written record of an oral production, the writer focuses this study on determining the degree of complexity and accuracy, and analyzing whether the different tasks change the level of learner’s oral performance. The results show that learner’s accuracy from both tasks remains in the same level. However, both task conditions, which do not allow speech plan, result in no improvement in accuracy level and a minor improvement in the complexity level.